Nanoscale gelatinase A (MMP-2) inhibition on human skin fibroblasts of Longkong (Lansium domesticum correa) Leaf extracts for anti-aging - Manosroi A. (2014)
Leaves of Longkong which collected from Chantaburi in Thailand were extracted by the hot and cold processes using three different solvents including water, chloroform and methanol. The crude extracts were tested for antioxidative activities, tyrosinase inhibition and in vitro cytotoxicity as well as the MMP-2 inhibition activity on human skin fibroblasts for anti-aging evaluation. The hot water crude extract showed the highest antioxidative activities (DPPH radical scavenging, metal ion chelating and lipid peroxidation inhibition) with the SC 50, CC 50 and IPC 50 values of 5.40±1.23, 32.31±0.84 and 3.29±0.30 mg/ml, respectively, and the highest tyrosinase inhibition activity with the IC 50 value of 0.49±0.23 mg/ml. The extract also showed no cytotoxicity on human skin fibroblasts with the cell viability of 80.52±15.16%. It demonstrated the anti-aging potential by having the pro and active MMP-2 inhibition activity, but lower than ascorbic acid of 1.28 and 1.12 times, respectively. The semi-purified extracts were prepared from this crude extract by solvent-solvent partition. The ethyl acetate soluble fraction showed higher activities (DPPH radical scavenging, metal ion chelating and tyrosinase inhibition) than the crude extract of 23.48, 71.80 and 2.58 times, respectively. This fraction exhibited similar pro and active MMP-2 inhibitory effect to the crude extract. The results from this study have indicated the possible application of the ethyl acetate fraction of the hot water crude extract from leaves of Longkong to be developed as an anti-aging product. Copyright © 2012 American Scientific Publishers All rights reserved.